2021
DOI: 10.3390/biology10090868
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Effects of Interval Training on the Immune System: A Systematic Review with Meta-Analysis

Abstract: Purpose: To summarize the evidence regarding the acute and chronic effects of interval training (IT) in the immune system through a systematic review with meta-analysis. Design: Systematic review with meta-analysis. Data source: English, Portuguese and Spanish languages search of the electronic databases Pubmed/Medline, Scopus, and SciELO. Eligibility criteria: Studies such as clinical trials, randomized cross-over trials and randomized clinical trials, investigating the acute and chronic effects of IT on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 80 publications
0
23
0
1
Order By: Relevance
“…Intermittent training is an aerobic training strategy that uses either rest or low-intensity-exercise periods between high-intensity periods. The primary concept behind this strategy is to allow more rigorous exercise periods than continuous high-intensity exercise 29 . Acute high-intensity interval training usually destabilizes the immune system, but chronic functional bouts may lead to immune system adaptations without altering leukocyte count 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Intermittent training is an aerobic training strategy that uses either rest or low-intensity-exercise periods between high-intensity periods. The primary concept behind this strategy is to allow more rigorous exercise periods than continuous high-intensity exercise 29 . Acute high-intensity interval training usually destabilizes the immune system, but chronic functional bouts may lead to immune system adaptations without altering leukocyte count 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Second, whether the decrease in the measured immune cells in response to HIIE in Khammassi’s study was of a magnitude sufficient to increase susceptibility to communicable diseases remains unknown, as the researchers did not attempt to investigate the potential relationship between those two factors. Elsewhere, impaired immune function resulting from a single HIIE session similar to those in the former study was not associated with an increased incidence of upper respiratory tract infections ( Fahiman et al, 2001 ), suggesting that altered immune function reported following a typical HIIE session ( Souza et al, 2021 ) may not be clinically relevant. Based on the currently available evidence, it appears only prolonged, fatiguing exercise can suppress immunity to the point where susceptibility to infection increases ( Davis et al, 1997 ).…”
mentioning
confidence: 59%
“…First, relying only on Khammassi’s findings when discussing the adaptations of the immune system to regular HIIE distorts the overall picture of the chronic effects of HIIE on immune function. Indeed, in a recent review of 36 studies, Souza et al (2021) found that, although acute HIIE can cause short-term immunosuppression, long-term HIIE leads to favourable changes in immune function. Second, whether the decrease in the measured immune cells in response to HIIE in Khammassi’s study was of a magnitude sufficient to increase susceptibility to communicable diseases remains unknown, as the researchers did not attempt to investigate the potential relationship between those two factors.…”
mentioning
confidence: 99%
“…This biphasic response is consistent with studies using strenuous or interval exercise. 6 , 9 , 55 , 56 , 57 , 58 The delayed exercise-induced lymphocytopenia may occur for several hours 5 , 6 , 55 and reflects the preferential movement of lymphocyte subtypes with potent effector functions (e.g., NK cells, γδ T cells, and CD8 + T cells) out of the blood 11 as an integral part of the physiological stress response to exercise. 11 Reduced lymphocyte count and function is associated with immunosuppression and increased risk for infection, 12 although this remains a controversial topic.…”
Section: Discussionmentioning
confidence: 99%